Experimental Analysis of Bio-Inspired Vortex Generators on a Blade with S822 Airfoil - Hector G. Parra; Hernan D. Ceron; William Gomez; Elvis E. Gaona (Energies, 2023)
Vortex generators are used in aircraft wings and wind turbine blades. These devices allow them to maintain a stable turbulent behavior in the wind wake. Vortex generators, or VGs, improve the transition from laminar to turbulent boundary layer regime, avoiding abrupt shedding. HAWT wind turbines have high rotational velocity. Currently, HAWT turbines are being redesigned with fixed vortex generators, achieving higher energy production. This paper presents a wind tunnel analysis of a fixed-wire blade with S822 airfoil and active VGs bio-inspired by the flight-stabilizing feathers of the peregrine falcon. Vibrations measured on the blade show a reduction in intensity at wind velocities close to 15 m/s. The measured wake velocities show fluctuations at higher tunnel wind velocities. An FFT spectral analysis of the wind wake velocities showed differences between the spectral components. When activating the VGs in oscillation at a constant frequency, a reduction of the vibrations on the blade was observed for wind velocities around 20 m/s.